2022
DOI: 10.3390/mps5030037
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Comparative Study of Eucalyptus, Basil, Cloves, Thyme, Pine Tree, and Tea Tree Essential Oil Biocide Efficacy

Abstract: Bio-colonization is a dynamic and multiphasic process headed by microorganisms. Conventional treatments to process affected stone materials include chemical biocides, whose formulations are mainly composed of quaternary ammonium salts(QAs), reported to be toxic for human health, dangerous for the environment, and not biodegradable. Accordingly, novel green and eco-friendly products are a promising alternative to treat stone materials deteriorated by microorganism colonization. In this study, the efficacy of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…BTE can be simply produced by soaking tea leaves or waste in boiling water to extract functional molecules from the boiling water. A previous study showed that caffeine, catechin, theanine, and theaflavin are the main biomolecules released from tea leaves into the BTE [ 19 , 20 ], as shown in Figure 1 . These biomolecules are rich in polyphenol, hydroxyl, and carboxylic acid groups [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…BTE can be simply produced by soaking tea leaves or waste in boiling water to extract functional molecules from the boiling water. A previous study showed that caffeine, catechin, theanine, and theaflavin are the main biomolecules released from tea leaves into the BTE [ 19 , 20 ], as shown in Figure 1 . These biomolecules are rich in polyphenol, hydroxyl, and carboxylic acid groups [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their effectiveness depends on the fungal species they treat. However, in front of this weakness, EOs can synergize with other EOs, achieving better biocide results than separately [198,199]. The hydrophobicity of EO compounds could be a weakness in easel painting conservation.…”
Section: Critical Comparison: Can Eos and Light Radiations Be A Good ...mentioning
confidence: 99%
“…In the study conducted by Macchia et al, 2022, the efficacy of pure EOs of eucalyptus, basil, cloves, thyme, pine tree, and tea tree was assessed in situ and compared to a conventional biocide based on quaternary ammonium salts. The tests revealed positive results concerning the synergy of the essential oils, showing a stronger biocide efficacy [ 52 ].…”
Section: Applicability Of Essential Oils In Food Productsmentioning
confidence: 99%